Estimation of future paddy production and sustainable land allocation in Malaysia: a polynomial approach - Munusamy, Subramaniam; Rajamoorthy, Yogambigai; Abdul Rahim, Khalid (Universiti Putra Malaysia Press, 2017)
This study examines the trend of paddy production and allocation of land for between 2014 and 2030 based on polynomial function. In order to gauge the time variance effect on sustainable land allocation for paddy production, short-term and long-term scenarios were used in estimating future paddy production and average yield. This study finds that with successive increases in the intensity of the long-term paddy productivity, the land required for paddy plantation in the future will be diminished. Additionally, the average yield per hectare explains the difference between long-term and short-term projection and emphasises the crucial need for improvement in research and development (R&D) and discovering alternative measures for domestic paddy production. Therefore, due to its increasing population, Malaysia has to ensure an efficient allocation of land for development and paddy plantation to cater to both current and future needs.